Analysis of the Role of Economic Factors on Foreign Direct Investment in Indonesia - Salsabila Arifin; Nazaruddin Malik; Hendra Kusuma (Jurnal Ekonomi Pembangunan, 2025)
This study aims to analyze the influence of economic growth, inflation, exchange rate, and labor force on the inflow of Foreign Direct Investment (FDI) in Indonesia. FDI plays a crucial role in supporting the economic development of emerging countries like Indonesia by contributing capital, transferring technology, creating employment opportunities, and enhancing productivity. The research uses annual time-series data from 1994 to 2023, sourced from the World Bank, and applies the Vector Error Correction Model (VECM) for analysis. The findings indicate that, in the long run, all four variables significantly affect FDI. Economic growth and the labor force have a positive impact, whereas inflation and the exchange rate exert a negative influence. In the short run, however, none of the variables show a statistically significant effect on FDI. These results highlight the importance of maintaining macroeconomic stability and improving labor quality to strengthen Indonesia's attractiveness to foreign investors.